THE CORRELATION BETWEEN MORPHOLOGICAL AWARENESS AND VOCABULARY MASTERY - Irma Khirana; Deri Sis Nanda; susanto susanto (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2023)
The primary aim of this research endeavour was to investigate the influence of students' language attitudes on their proficiency in acquiring the English language. The primary aim of this study is to investigate the influence of students' attitudes on their language acquisition and to analyse the importance of various mindsets throughout the process of learning. The current study utilises a blend of qualitative research methods to evaluate data obtained from a cohort of 16 students in their seventh semester at FKIP, Universitas Bandar Lampung. The main aim of this study was to collect data on students' perspectives regarding the study of English as a Foreign Language (EFL), employing questionnaires and interviews as the principal research tools. The research findings unveiled a significant association between students' favourable sentiments towards the English language and their comprehensive academic achievement in the discipline. The study highlights three separate components of attitudes, specifically cognitive, affective, and behavioural, that exert a substantial impact on academic performance. The results suggest that students' attitudes towards language acquisition significantly influence their overall academic performance. Furthermore, the study uncovered that the linguistic attitudes of students exerted a significant impact on their proficiency in acquiring the English language. The significance of understanding students' attitudes towards the study of foreign languages is emphasised in order to improve educational results and academic accomplishments. The findings of this study have the potential to offer significant contributions to educators in the development of English-learning curricula that promote student engagement and excitement.